Synthesis of arotinoid acid and temarotene using mixed (Z)-1,2-bis(organylchalcogene)-1-alkene as precursor - Guerrero, Palimecio G.; Oliveira, Paulo R. de; Baroni, Adriano C. M.; Marques, Francisco A.; Labes, Ricardo; Hurtado, Gabriela R.; Dabdoub, Miguel J. [UNESP] (Elsevier B.V., 2012)
An efficient and novel total synthesis of the two bioactive retinoids temarotene and arotinoid acid (TTNPB) is described. The key steps in this process include the regio and stereoselective hydrotelluration of thioacetylene 9 and Te/Li transmetalation of mixed (Z)-1,2-bis(organylchalcogene)-1-alkene (Z)-3. The subsequent reaction involving the beta-phenylthio vinyl lithiated intermediate 10 with dimethyl sulfate gave the (E)-vinyl sulfide 11. The Ni+2 cross-coupling of 11 with the corresponding phenylzinc bromide and p-oxazoline phenylzinc bromide 12 afforded the respective temarotene 2 and retinoid-oxazoline substituted 13. Finally, compound 13 was deprotected with HCl to furnish arotinoid acid (TTNPB) 1. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Retinoid; Temarotene; Arotinoid acid (TTNPB); Synthesis; (Z)-1,2-bis(organylchalcogene)-1-alkene; Anticancer